The school skeleton - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2003)
At Green Lawn Elementary, the entire school becomes involved in a mystery when Mr. Bones, the skeleton in the nurse$1 (Bs office, disappears.s
Keywords: Skeleton -- Fiction; Lost and found possessions -- Fiction; Schools -- Fiction; April Fools$1 (BDays -- Fiction; Mystery and detective stories